Pelatihan Pembuatan Penelitian Tindakan Kelas di SMPN 14 Banjarbaru - Saman Abdurrahman; Lilis Harianti Hasibuan; Mochammad Idris; Na’ímah Hijriati; Juwita Lasterina; Sheryn Amelia Puteri; Gusti Muhammad Rosyadi; Audinta Sakti Firmansyah; Nor Hidayati (Universitas Mathla'ul Anwar Banten, 2022)
CLASSROOM ACTİON RESEARCH-MAKING TRAİNİNG IN SMPN 14 BANJARBARU. Classroom Action Research is practical research intended to improve classroom learning. This research is one of the efforts of teachers or practitioners in the form of various activities carried out to improve and or improve the quality of learning in the classroom. Classroom Action Research can be interpreted as a process of studying learning problems in the classroom through self-reflection to solve these problems by carrying out various planned actions in real situations and analyzing any effects of the treatment. Classroom Action Research is one of the scientific publications in the context of sustainable teacher professional development aimed at improving and improving the quality of learning processes and outcomes or the quality of education in general. The article describes the implementation of Classroom Action Research Assistance Activities and Scientific Article Writing at SMPN 14 Banjarbaru, South Kalimantan. This activity is important because it can stimulate the creativity of teachers to conduct Classroom Action Research. The benefit of this activity is that teachers become more and more skilled in choosing or making appropriate learning methods for their students from time to time. Another impact of this activity can certainly improve teacher careers to a higher level.